Defence Innovation and Women’s Participation in the Armed Forces: An Analysis of PISFLEMB - Schwether, Natalia Diniz [UNESP]; Azevedo, Carlos Eduardo Franco (Pontifícia Universidade Católica do Rio de Janeiro, Instituto de Relações Internacionais, 2024)
Throughout history, on several occasions, technological advances have driven fundamental changes in the defence sector. The increasing availability and technological dependence led to the redefinition of pre-established functions, the modification of the main missions, and even the rearticulation of traditional values ​​of the military institution. From this perspective, the article aims to answer the following question: in what way did the Project for the Integration of Female Personnel in the Line of Military Warfare Education (PISFLEMB) promote innovation in the Brazilian Armed Forces? It is argued that the participation of women in a traditionally male institution is responsible for generating organizational innovation, both in values and conduct. Data will be collected through official documents and primary sources as modelled for analysis of military innovations. The study is distinguished by the understanding that innovations in the defence sector are an opportunity for transformation and a stimulus for changing patterns of conduct.

Ao longo da história o avanço tecnológico impulsionou, por diversas vezes, mudanças fundamentais no setor de defesa. A crescente disponibilização e dependência tecnológica provocou a redefinição de funções pré-estabelecidas, a modificação das principais missões e, até mesmo, a rearticulação de valores tradicionais da instituição militar. A partir dessa perspectiva, o artigo visa responder à pergunta: de que forma o Projeto de Inserção do Sexo Feminino na Linha Ensino Militar Bélico (PISFLEMB) promoveu inovação nas Forças Armadas brasileiras? Argumenta-se que a participação de mulheres em uma instituição tradicionalmente masculina é responsável por gerar uma inovação organizacional, tanto em valores quanto na conduta. Serão coletados dados por meio de documentos oficiais e fontes primárias conforme modelo para análise das inovações militares. O estudo distingue-se em virtude da compreensão de que inovações no setor de defesa são uma oportunidade para a transformação e um estímulo para a alteração de padrões de conduta.
Inovação em Defesa e Participação Feminina nas Forças Armadas: Uma Análise do PISFLEMB
Keywords: innovation; women; Armed Forces; technology; Brazil; inovação; mulheres; Forças Armadas; tecnologia; Brasil